2016
DOI: 10.1519/jsc.0000000000001331
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Types of Warm-Up Upon Repeated-Sprint Performance in Experienced Soccer Players

Abstract: van den Tillaar, R and von Heimburg, E. Comparison of two types of warm-up upon repeated-sprint performance in experienced soccer players. J Strength Cond Res 30(8): 2258-2265, 2016-The aim of the study was to compare the effects of a long warm-up and a short warm-up upon repeated-sprint performance in soccer players. Ten male soccer players (age, 21.9 ± 1.9 years; body mass, 77.7 ± 8.3 kg; body height, 1.85 ± 0.03 m) conducted 2 types of warm-ups with 1 week in between: a long warm-up (20 minutes: LWup) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 28 publications
5
21
0
3
Order By: Relevance
“…In a recent study of semi-professional soccer players [16], the authors observed that a pre-match warm-up of 25 min, despite improving players’ perception of being prepared to play a game, decreased sprint performance over 10 m and 20 m. The players in this study reported high values ​​of subjective perceived exertion (RPE) and RPE training load at the end of the warm-up protocol [16], which may suggest that the warm-up with a duration close to 25 min caused fatigue in the soccer players and consequently a decrease in their physical performance. Similar results were obtained in other studies carried out with soccer players, where it was also observed that with longer duration of warm-up the RPE was significantly higher than for the short warm-up [17-19]. Due to these contradictory results among the different studies and in order to determine whether a reduction in the duration of the warm-up may be more effective, it would be interesting to carry out further studies to analyse the effects of same-task warm-up protocols with different durations in soccer players.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…In a recent study of semi-professional soccer players [16], the authors observed that a pre-match warm-up of 25 min, despite improving players’ perception of being prepared to play a game, decreased sprint performance over 10 m and 20 m. The players in this study reported high values ​​of subjective perceived exertion (RPE) and RPE training load at the end of the warm-up protocol [16], which may suggest that the warm-up with a duration close to 25 min caused fatigue in the soccer players and consequently a decrease in their physical performance. Similar results were obtained in other studies carried out with soccer players, where it was also observed that with longer duration of warm-up the RPE was significantly higher than for the short warm-up [17-19]. Due to these contradictory results among the different studies and in order to determine whether a reduction in the duration of the warm-up may be more effective, it would be interesting to carry out further studies to analyse the effects of same-task warm-up protocols with different durations in soccer players.…”
Section: Introductionsupporting
confidence: 90%
“…In soccer, warm-up protocols with different durations [14] ranging from 5 min [12] to 35 min [13] have been used. Although several studies have analysed the effects on soccer players’ physical performance of short-duration and high-intensity warm-up protocols [30], longer protocols [31], or protocols with different types of tasks and durations [17-19,32,33], few studies have analysed whether the same type of warm-up (same exercises) with different durations could have different effects on the physical performance of soccer players [11,17]. In the present study, whereas the 25 min protocol caused a decrease in 10 and 20 m sprint performance and the 15 min protocol did not induce any change in acceleration, vertical jump or change of direction ability, the 8 min protocol was the only one that improved performance in the 10 and 20 m sprint.…”
Section: Discussionmentioning
confidence: 99%
“…The first 40-m effort was at a self-estimated intensity of approximately 60% of estimated maximal sprinting velocity; each 40-m effort thereafter increased by approximately 5% until they reached 95% of maximal self-estimated intensity. In each rest period, one of seven dynamic flexibility exercises for the shoulders, hip, knee, and ankle joints was completed, starting with the shoulders and working downwards to increase the range of motion of the different joints, as described in detail by van den Tillaar et al [23] and van den Tillaar and von Heimburg [24]. After the warm-up, the participants had 5 minutes of active rest (easy walking and standing) before they performed one of the three protocols.…”
Section: Methodsmentioning
confidence: 99%
“…The testing was conducted on two different occasions, consisting of one familiarization day and one testing day, which were conducted with 2−7 days between each other. All the sessions started with a standardized warm-up protocol as specified by van den Tillaar and von Heimburg [27], which consisted of a total 10 min with 1 of 7 different dynamic stretch exercises that were performed in the recovery period of 60 s between the 8 x 40 m runs, and the runs were performed at self-estimated intensity, starting from 60% of maximal sprinting velocity and then increasing by 5% until reaching 95% [27]. After 2 min rest, the subjects performed two submaximal runs in the COD test with 2 min recovery in between.…”
Section: Methodsmentioning
confidence: 99%